Avaliação dos efeitos do alho (Allium sativum L.) sobre o colesterol plasmático em coelhos com hipercolesterolemia induzida - Sant'Anna, Bruna Klassa Cardoso [UNESP] (2010)
The use of plants in treatments of diseases or even in the cure of them is a high difused popular tradition, and several works talk about the therapeutic and pharmacological properties of garlic in the reduction of hyperlipidaemias. The objective of the present work was to investigate the influence of garlic (Allium sativum) aqueous extract treatment on the serum cholesterol of rabbits in experimental hypercholesterolemia. The animals were divided in G1 (control group) and G2 (group with garlic treatment). The experiment was developed in 3 phases: during the 1st phase, all the animals received regular diet for evaluation of basal cholesterol; in the 2nd phase all the animals received supplemented diet until the end of the experiment, in order to develop hypercholesterolemia and in the 3rd phase, the animals of G2 received the garlic treatment. The cholesterol registered on the 1st phase was 39,94 ± 9,57mg/dL. On the 2nd phase, there was an increase on the serum cholesterol level in both groups – higher than 100mg/dL. Concerning the treatment, garlic didn’t reduce the serum cholesterol in rabbits